Geobiology: teaching the evolution of life on Earth (Research, Society and Development, 2018)
The Earth's geological and ecological histories are directly linked to understanding the major processes that constituted and modified the Earth, as well as uncovering a part of the planet's past, can help us understand the current time and still glimpse the future. The Geobiology extension project, developed at the Fundação Comunitária de Ensino Superior de Itabira - FUNCESI (MG), has as main objective the dissemination of the natural sciences, seeking an understanding of the formation, evolution and future of life on Earth. Thus, this study aims to analyze the perception about the geosciences concepts of 413 students who visited the Geobiology project in the year 2017. For such, a same questionnaire was applied before and after the development of the activities related to the project. From the results obtained, it was possible to notice the assimilation of concepts related to the age of the Universe and the Earth, on the other hand, the use of explanations, images and videos was not enough for a satisfactory understanding of the concepts associated with plate tectonics and first forms of life on Earth. It should be noted that the use of fossil replicas, as well as the manipulation of minerals and rocks, besides making the activities more dynamic, were described by the participating students as the most cooler part of the project. Thus, it is expected that this project will provide students with a better understanding of the correlation between the various natural sciences and their applications in everyday life, in addition to raising the importance of environmental preservation in all sectors of society.